Three dimensions of computational journalism. Intersections with information sciences - Codina, Lluís (Anuario ThinkEPI, 2016)
Systematic presentation of three dimensions of computational journalism characterized by their intersections with information science: Content curation, SEO applied to communication, and information seeking and verification. Intersections between various disciplines are discussed.